(untitled) (Al-Qantara, 2024)
AI is at the forefront of productivity, streamlining work processes and women and enriching decision-making processes. With AI mapping, which can include elements of predictive analytics, ML and NLP, it is easy to enhance the supply chain functions, recognise operational deviations in time, and delegate repetitive tasks to the automation. This shift improves efficiency and allows businesses to focus human capital on generating value and adaptability. However, there are still issues of AI integration, data quality, and how to ensure that AI operations and supply chain management work in synergy with human supervisors and workers. This research used a systematic literature review approach using Google Scholar, IEEE Xplore, and Scopus. The results show that the key to successful implementation is to advance constant change and learning and cultivate good human/machine synergy for even long-term and stable growth in the current contexts of the dynamic and complex business environment.